Surgery for Rheumatic Heart Disease in Nepal - Koirala, Bhagawan (Nepalese Heart Journal, 2016)
Rheumatic heart disease is still very common in the developing world.Nepal is no exception.lack of health insurance for most people and monitoring of the PT/INR in a long run pose a significant financial challenge to an ordinary Nepalese family and is associated with significant lifestyle issues of the patients. This article presents the surgical issue in the management of rheumatic heart disease in Nepal.Nepalese Heart Journal 2016; 13(2): 11-14